2017
DOI: 10.1038/s41598-017-08790-5
|View full text |Cite
|
Sign up to set email alerts
|

Milk microbiome and bacterial load following dry cow therapy without antibiotics in dairy cows with healthy mammary gland

Abstract: Preventive infusion of antibiotics in the mammary gland of cows consumes 11 tons/year of medically relevant antimicrobials, yet, this practice might not be critical to prevent new infections in the healthy mammary gland of cows. Here, we used next-generation sequencing and quantitative real-time PCR to determine the impact of dry cow therapy without antibiotics on milk microbiome and bacterial load, respectively. Cows diagnosed as negative for mastitis at dry off were randomly allocated to receive antibiotic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
73
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 43 publications
16
73
2
1
Order By: Relevance
“…Bonsaglia et al. () reported that Corynebacterium spp. ( Corynebacteriaceae ) and Psychrobacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonsaglia et al. () reported that Corynebacterium spp. ( Corynebacteriaceae ) and Psychrobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Although increasing data for milk microbiota, determined by next‐generation sequencing (NGS) analyses, have become available, the results were highly variable between experiments and the understanding of high‐throughput data is largely complicated by factors such as milk quality control and mastitis prevention (Bhatt et al., ; Bonsaglia et al., ; Doyle et al., ; Falentin et al., ; Kuehn et al., ; Oikonomou et al., ; Young, Hine, Wallace, Callaghan, & Bibiloni, ). Furthermore, information on the milk microbiota of cows managed by AMS is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Such DCT was suspected to affect and disturb the microbiota of healthy mammary gland. Bonsaglia et al (2017) evaluated this hypothesis by determining the effect of DCT with teat sealant alone or with antibiotics (ceftiofur hydrochloride) on non-mastitic cows. They found that omitting antibiotics from DCT has no effect on the milk microbiota at dry off and 7 days postpartum in the subsequent lactation.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Nevertheless, obligate anaerobes, including Bifidobacterium and Veillonella, have also been isolated, suggesting that the living part of milk microbiota may not have been fully or properly explored so far. The biodiversity of the milk microbiota (Kuehn et al, 2013) as well as its resilience following infection or antibiotic treatment (Ganda et al, 2016;Bonsaglia et al, 2017;Derakhshani et al, 2018c) suggests that milk microbiota is not limited to non-viable bacteria that are associated or not to immune cells and invites us to further address this issue using high-throughput culturedependent methods. Similar issues have been raised concerning other microbiota associated with meconium, placenta, amniotic fluid, and uterus as recently reviewed by Perez-Muñoz et al (2017).…”
Section: Does a Live Microbiota Exist In Milk?mentioning
confidence: 99%
“…A antibioticoterapia no PS foi desenvolvida na década de 40, sendo inicialmente utilizada para controlar mastites de verão (PEARSON, 1951 MCDOUGALL et al, 2009;BONSAGLIA et al, 2017).…”
Section: Bases Antimicrobianas Usadas Na Tvsunclassified